The Role of Motivation and Commitment in Teachers’ Professional Identity - Ma, Dongmin (Frontiers in Psychology, 2022)
Teacher professional identity is a feature of an educator that must be planned in an extended, steady, and continuing procedure and typically forms in any particular academic and social setting. As the education profession is largely stressful, it calls for consistent commitment and also motivation to help alleviate the difficulties. Indeed, the educators’ efficiency and effectiveness are mediated by these constructs to both school problems as well as the teaching work as a whole. Besides multiple factors affecting teacher professional identity, commitment and motivation have important functions that are addressed by this mini-review of literature. Briefly, several implications are proposed for the EFL instructional recipients.